FAKTOR PENYEBAB KEENGGANAN ISTERI MENGAJUKAN GUGAT CERAI TERHADAP SUAMI YANG MELANGGAR SIGHAT TAKLIK TALAK DI KECAMATAN KAUR SELATAN KABUPATEN KAUR - Harizon, Sri Dian (UIN Fatmawati Sukarno Bengkulu, 2017)
This study raises the issue of the causes of the reluctance wife filed a divorce against her husband who violate sighat taklik divorce and understanding with their wives taklik divorce in marriage as well as the legal implications of the breach taklik divorce for a marriage. The purpose of this study was to determine the factors causing reluctance wife filed a divorce against her husband who violate sighat taklik divorce and understanding wives District of South Kaur Kaur District with their taklik divorce in marriage as well as to know the legal implications of the breach taklik divorce for a marriage. This study uses empirical juridical law starts from the primary data / basic data is data obtained directly from informants selected are six wives whose husbands abuse sighat taklik divorce in the district South Kaur Kaur regency. The data collection techniques used were observation, interview and secondary data collection. When the data to do the data analysis by descriptive normative. The results showed that the wives of the District Kaur Southern District Kaur assume that sighat taklik divorce in a marriage is only limited pledge of marriage and does not quite understand that sighat taklik divorce is guaranteed protection of self-wives while factors causing reluctance wife filed a divorce against husband sighat abuse taklik divorce in the district of South Kaur Kaur District is because of shame to the neighbors and the psychological impact of small children, not understanding the process of the divorce to the religious courts, and embarrassed by the title of a widow who still put it negatively as a widow in society